TOBACCO CARCINOGEN METABOLITES AND DNA ADDUCTS AS BIOMARKERS IN HEAD AND NECK CANCER: POTENTIAL SCREENING TOOLS AND PROGNOSTIC INDICATORS - Khariwala, Samir S. (Head Neck, 2011)
Head and neck squamous cell carcinoma (HNSCC) is one of many cancers that are strongly associated with tobacco use. Whereas HNSCC is often seen in tobacco users, many tobacco users do not develop carcinoma; and the differences between smokers with and without HNSCC are poorly studied to date. Some smokers may be inherently more susceptible to developing carcinoma due to patterns of tobacco use, innate metabolism of carcinogens, or altered excretion. Identifying those smokers at greatest risk for HNSCC would have great benefit through targeted smoking cessation efforts and enhanced surveillance. One approach to better understand the extent of exposure to, and metabolism of, tobacco carcinogens is through the use of tobacco-specific metabolites. Tobacco-specific metabolites can identify patterns of dose, exposure, and metabolism, and perhaps ultimately characterize the important differences between smokers who develop HNSCC and smokers who do not.